The effect of plasminogen activator inhibitor type 1 on apoptosis - Schneider, David J.; Chen, Yabing; Sobel, Burton E. (Thrombosis and Haemostasis, 2008)
Plasminogen activator inhibitor type-1 (PAI-1), an inhibitor of plasminogen activators, inhibits formation of plasmin and plasmin-mediated proteolysis. Apoptosis,or programmed cell death, is a potentially important phenomenon in mediating overall cell death. This review focuses on the influence of PAI-1 on apoptosis. Greater expression of PAI-1 has been associated with increased survival of cells and resistance to apoptosis. PAI-1 appears to influence apoptosis by decreasing cell adhesion (anoikis) as well as its effect on intracellular signaling. Mechanisms by which PAI-1 may render a cell resistant to apoptosis include its ability to inhibit generation of plasmin,its ability to inhibit caspase 3, and its ability to inhibit cell adhesion mediated by vitronectin. Inhibition of caspase 3 by PAI-1 may divert intracellular signalling from induction of apoptosis to induction of proliferation.
Keywords: Plasminogen activator inhibitor; apoptosis; vascular remodelling; cancer